Analisis Proksimat Pakan Ikan Nila (Oreochromis niloticus) Berbasis Tepung Bekicot, Azolla, dan Kunyit sebagai Suplementasi Fitobiotik - Muhammad Kelvin S. Pontoh; Tusaban Tusaban; Dewi Shinta Achmad; Nur Jihan Fareranty Piu (Student Scientific Creativity Journal, 2026)
High feed costs remain a major constraint in Nile tilapia (Oreochromis niloticus) aquaculture, requiring alternative feed formulations based on local ingredients with adequate nutritional quality. This study aimed to evaluate the proximate composition of fish feed formulated from snail meal, Azolla meal, and turmeric as a phytobiotic supplement. The study used an experimental method with a Completely Randomized Design consisting of three treatments and three replications. The feed formulations were P1, consisting of 55% snail meal, 25% Azolla meal, 5% turmeric, 10% corn flour, and 5% tapioca flour; P2, consisting of 39% snail meal, 39% Azolla meal, 7% turmeric, 10% corn flour, and 5% tapioca flour; and P3, consisting of 25% snail meal, 51% Azolla meal, 9% turmeric, 10% corn flour, and 5% tapioca flour. The analyzed parameters included protein, moisture, fat, ash, crude fiber, and carbohydrate contents. Data were analyzed using analysis of variance followed by the Least Significant Difference test. The results showed that feed formulation significantly affected all proximate parameters. P3 produced the highest protein content of 43.87%, fat content of 3.68%, crude fiber of 3.11%, and carbohydrate content of 7.28%, while also producing the lowest ash content of 28.46%. Moisture content ranged from 1.11% to 1.30%, indicating good feed storage stability. These findings demonstrate that the integration of snail meal, Azolla, and turmeric can improve the nutritional quality of alternative Nile tilapia feed and support locally based sustainable aquaculture feed development.